Professional Windows phone 7 application development : building applications and games using Visual Studio, Silverlight, and XNA - Randolph, Nick, 1978-; Fairbairn, Christopher (Wrox programmer to programmer, 2011)
A one-of-a-kind book on Windows Phone 7 development. While numerous books cover both Silverlight and XNA, there lacks a resource that covers the specifics of Windows Phone 7 development. This book fills that void and shares the specifics of building phone applications and games. You'll learn how to get started with designing, building, testing, and deploying mobile applications for Windows Phone 7. Working examples used throughout the book cover how to design and layout a Windows Phone 7 application, interact with the device, and even sell your applications.: Fills the void in the market for a.